2018
DOI: 10.1123/jcsp.2016-0036
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure and Gender Invariance Testing for the Sport Anxiety Scale-2 (SAS-2)

Abstract: This study aimed to provide further psychometric validation of the Sport Anxiety Scale-2 (SAS-2) by assessing the factor structure, invariance across gender, and convergent and divergent validity of the SAS-2 by correlating both related (i.e., anxiety sensitivity, brief fear of negative evaluation, intolerance of uncertainty, and negative affect) and unrelated constructs (i.e., positive affect, self-confidence). A total of 542 current and former competitive athletes completed a questionnaire through Amazon’s M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
(48 reference statements)
3
6
0
Order By: Relevance
“…Multiple group CFAs also showed that the CAS measures coronavirus related fear and anxiety in a similar way across age, gender, and race groups. Not only did these results replicate the findings of the original CAS research, they were also in keeping with other factor invariance studies of anxiety measures as well (Bunnell et al, 2013;Kyriazos et al, 2018;Madrigal et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…Multiple group CFAs also showed that the CAS measures coronavirus related fear and anxiety in a similar way across age, gender, and race groups. Not only did these results replicate the findings of the original CAS research, they were also in keeping with other factor invariance studies of anxiety measures as well (Bunnell et al, 2013;Kyriazos et al, 2018;Madrigal et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…Finally, the 15-item scale achieved high reliability indices and a good fit of the theoretical model to the data in each of the extracted age groups 9 . Satisfactory validity and reliability indices of the scale were also confirmed in studies conducted in different countries, e.g., Spain 10 , Brazil 6 , 11 , Malaysia 12 , U.S. 13 and Korea 14 .…”
Section: Introductionsupporting
confidence: 56%
“…The hierarchical model and the 3-factor model had a significant advantage of fitting to empirical data over the single-factor model, which confirms the validity of separating the theoretically justified three subscales of the SAS-2 scale. Comparing the obtained results with the results of other authors, it can be concluded that both hierarchical and the 3-factor model of the Polish version of the scale estimated on the whole group of respondents had worse fit to the data than the models presented by the authors of the scale 9 , the models of the Spanish version of the scale 10 and the 3-factor model of the American version of the scale 13 . In turn, the models of the Polish version of the scale obtained a better fit to the data than the model (three factor model without correlating errors for items) of the Brazilian version of the scale 6 .…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations